The prognostic role of serum uric acid levels in preeclampsia: A meta‐analysis. Issue 5 (27th April 2020) - Bellos, Ioannis; Pergialiotis, Vasilios; Loutradis, Dimitrios; Daskalakis, Georgios
Abstract: This meta‐analysis aims to compare serum uric acid levels among preeclamptic and healthy pregnant women across the various trimesters and provide a summary of the effect size of this biomarker in predicting adverse pregnancy outcomes. MEDLINE, Scopus, CENTRAL, Clinicaltrials.gov, and Google Scholar databases were systematically searched from inception. Observational studies were held eligible if they reported serum uric acid among preeclamptic and healthy pregnant women. Meta‐analysis was conducted regarding uric acid concentration, diagnostic accuracy, and association with perinatal outcomes. The credibility of evidence was appraised using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework. The analysis included 196 studies, comprising 39 540 women. Preeclampsia was associated with significantly elevated uric acid levels during the 1st (mean difference [MD]: 0.21 mg/dL, 95% confidence intervals [CI]: 0.06‐0.35) trimester, 2nd (MD: 1.41 mg/dL, 95% CI: 0.78‐2.05) trimester, and 3rd (MD: 2.26 mg/dL, 95% CI: 2.12‐2.40) trimester. Higher uric acid was estimated for severe preeclampsia, eclampsia, and hemolysis, elevated liver enzymes, low platelet syndrome. The sensitivity for adverse perinatal outcome prediction ranged from 67.3% to 82.7% and the specificity from 47.7% to 70.7%. In conclusion, it is suggested that serum uric acid levels are increased in preeclampsia and can be used to predict disease severity and pregnancy complications. Future prospective studies should verify these outcomes, assess the optimal cutoffs, and incorporate uric acid to combined predicting models.